INFLUENCIA DE LAS COBERTURAS DE ENCINAS , Quercus ilex subsp. ballota , EN LA ROTURA DE LOS PERFILES TERMICOS VERTICALES - Escudero Garcia, J. C.; Cabezas Fernández, J.; Lavado Contador, F. (CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993, 1993)
Vegetation cover acts intensely on vertical temperature profiles, breaking up their structure. For the particular case of holm oak parkland (dehesas) forests systems, these will affect the vertical temperature gradient by modifying it more or less sharply as a function funtamenta1ly of the height and characteristics of the canopy, the density of trees ánd of foliage load. The study was carried in Cheles (Badajoz), and consisted in periodic measurements of the temperature variations in the profile. The results show quantitatively the influence of arboreal systems on the vertical structure of air and soil temperatures. A characterlzation is thereJore given of the thermal impact that intense pruning and destruction of holm oaks have on the vertical profIle, especially that of he soil.
The following values have no corresponding Zotero field: periodical: CONGRESO FORESTAL ESPAÑOL - Lourizán 1.993
Keywords: gradients; impact; Quercus ilex; Temperature